Nalmefene: A Novel Drug for an Old Disorder - Marazziti, Donatella; Presta, Silvio; Baroni, Stefano; Mungai, Francesco; Piccinni, Armando; Mucci, Federico; Dell128;™Osso, Liliana (Current Medicinal Chemistry, 2015)
Alcoholism is an increasing problem all over the world, and nowadays especially amongst teenagers. Although several drug treatments have been proposed for this condition, only a few have demonstrated a significant efficacy. Nalmefene, a novel compound that combines opioids mu-receptors antagonism and kappa-receptors partial agonism, was recently approved by the European Medicine Agency for the treatment of alcoholism. This drug can be very helpful in reducing the alcohol intake, and, as such, it can be considered one of the first and fundamental steps towards alcohol abstinence. The aim of this review is to discuss and comment on the available literature on nalmefene, as well as on novel treatment strategies of this condition (and perhaps of other addictions) opened by this latest pharmacological approach.
Keywords: opioids